A Study on the psychological distress in patients for screening and recalled Mammography Examinations in Selayang Hospital / Nur Hidayah Basri - Basri, Nur Hidayah (2015)
Breast cancer is the most common types of cancer in women around the world including Malaysia. About one in 19 women in Malaysia are at risk, compared to one in eight in Europe and the United States (Wahid, 2012). Nowadays, screening programme for breast cancer has been organized widely around Malaysia either by a non-government or government organizations. Concerns regarding the effects of psychological distress and anxiety have been arising among patients who had undergo mammography examinations for screening and recalled examinations. Psychological effects may include anxiety, worrying about having the cancer and depression while following the examinations (Schou Bredal et al., 2013). The problems regarding the psychological effects bring a huge impact on patients to come for the mammography examinations. Thus, a study is conducted to determine a specific level of psychological distress in mammography patients for both screening and follow-up examinations. This research aim is to study the level of anxiety and depression for mammography examinations and to document the willingness of patients to come for their mammography examinations and recommend this examination to other women. It is specifically studies on mammography patients in X-Ray Department of Selayang Hospital, Selangor, Malysia. This study is based on the data obtained from a questionnaire constructed from the Hospital Anxiety and Depression Scale (HADS) and the Life-Orientation Test Revised (LOT-R) and distributed to patients for mammography examinations. Then, the data collected was transferred and analyzed in SPSS data statistic software for evaluation. The research suggested that the anxiety and depression level of women who came for mammography examinations is managed well and contribute to the improvement in awareness about the breast cancer and the importance of mammogram examinations in detecting breast abnormality especially for women ages 40 – 70 years old. It is hope that the study can contribute to the improvement of anxiety and depression management to encourage women to adhere with mammography examination annually scheduled.